Beyond educational attainment: The importance of skills and lifelong learning for social outcomes. Evidence for Europe from PIAAC. (11th April 2017) - Vera‐Toscano, Esperanza; Rodrigues, Margarida; Costa, Patricia
Abstract: Empirical evidence suggests that educational attainment nurtures people's social outcomes and promotes active participation in society and stability. However, it is unclear to what extent other types of human capital also correlate with social outcomes. Hence, we explored the opportunity offered by the PIAAC survey through its provision of information on educational attainment, observed individual key skills proficiency, and participation in adult education and training (adult lifelong learning). We therefore studied the association between these human capital variables and social outcomes, and more specifically interpersonal trust and participation in volunteering activities. Results revealed that these social outcomes were affected not only by the formal qualification obtained, determined by the education variable, but also throughout the life‐cycle. Indeed, education and training when undertaken during adult life have a significant impact, especially on volunteering. The fact that the skill proficiency also plays a significant role is extremely relevant, as skills are more likely to change over the life‐cycle, either in a positive or negative way. Whilst the formal education received is constant after exiting the educational system, skills reflect competences more accurately: first, because those with the same level of education may have different skill levels because of differences in the quality of education or ability; second, because skills can vary over time. For example, they may increase with work experience or informal education, or decrease as a result of depreciation and ageing. These findings suggest that social outcomes are prone to be affected by many factors other than formal education, suggesting that policy makers can implement recommendations even after formal education has been completed.